Religiosity and Compassionate Love in Mother of Children with Autism Spectrum Disorder - Ratri Desiningrum, Dinie; Retno Suminar, Dewi; Retno Surjaningrum, Endang (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The aim of the study was to observe the correlation between religiosity and compassionate love in mothers of children with ASD.Methodology: The study is a quantitative study using correlational design. A total of 120 mothers of children with ASD were selected using purposive sampling quota, based on the following criteria: mothers of children aged 5-17 years with ASD living in Central Java. Data were obtained using two scales namely Compassionate Love Scale dan Centrality of Religiosity Scale. Pearson’s Correlation Analysis was used to find the correlation between variables. Furthermore, another analysis was conducted to determine the contribution of dimensions of religiosity to compassionate love.Result: The analysis resulted in the value of F=5.122, with significance level 0.007, shows that there is a correlation between religiosity and compassionate love. The coefficient of correlation shows that the correlation between religiosity and compassionate love in mothers of children with ASD was 0.687. Positive correlation indicates that the higher religiosity leads to the higher compassionate love in mothers of children with ASD. The dimensions of religiosity that contribute significantly to compassionate love are individual practice, religious experience, and the intellectual dimension.Applications/Originality/Value: The implication of the study is to provide a knowledge on studies related to parenting children with ASD, especially on mothers’ compassionate love, to make the Government aware of the need for better religious facilities to and focus on increasing the quality of religiosity in its citizen, especially in mothers of children with ASD.